2012
DOI: 10.1371/journal.pone.0041136
|View full text |Cite
|
Sign up to set email alerts
|

Selective Attention Increases Choice Certainty in Human Decision Making

Abstract: Choice certainty is a probabilistic estimate of past performance and expected outcome. In perceptual decisions the degree of confidence correlates closely with choice accuracy and reaction times, suggesting an intimate relationship to objective performance. Here we show that spatial and feature-based attention increase human subjects' certainty more than accuracy in visual motion discrimination tasks. Our findings demonstrate for the first time a dissociation of choice accuracy and certainty with a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…(1). In accordance with our previous study 12 , paired t-tests on these standardized measures revealed not only significant increases for decision accuracy and choice confidence with attention (both t-tests: Po0.001; Fig. 1e, positive D z-values for each category), but also a significantly stronger increase of the confidence measure (t-test: P ¼ 0.001; labelled grey in Fig.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…(1). In accordance with our previous study 12 , paired t-tests on these standardized measures revealed not only significant increases for decision accuracy and choice confidence with attention (both t-tests: Po0.001; Fig. 1e, positive D z-values for each category), but also a significantly stronger increase of the confidence measure (t-test: P ¼ 0.001; labelled grey in Fig.…”
supporting
confidence: 91%
“…Reflecting the dependency of task difficulty on motion coherence, discrimination performance increased for higher motion coherences in both attention conditions as expected 12,14 . Furthermore, we found higher sensitivity to visual motion for valid as compared with invalid cues as indicated by higher mean accuracy with attention for each of the four coherence levels (mean accuracy for 10/20/30/ 40% coherence, valid cues: 0.53/0.77/0.87/0.90; invalid cues: 0.42/0.63/0.75/0.83; Fig.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…These effects are the signatures of attention in humans and nonhuman primates (2,3,30). In addition, in chickens, as in humans, spatial cueing increased choice certainty (21).…”
Section: Discussionmentioning
confidence: 93%